The Influence of Reproductive Health Education On Adolescents' Knowledge and Attitudes about HIV/AIDS At Sman 7 Bengkulu City. - Sri Yunita; Nurul Fatimah Susanti; Nurul Aryastuti (Jurnal Dunia Kesmas, 2026)
The adolescent transition period is marked by an identity search process that is vulnerable to risky sexual behavior, a primary factor in HIV/AIDS transmission. Preventive efforts through structured education are highly necessary. This study aimed to determine the effect of reproductive health education on increasing knowledge and changing adolescent attitudes about HIV/AIDS at SMAN 7 Bengkulu City. This was a quantitative analytic study using a One-Group Pretest-Posttest Design, conducted in October 2025. The sample consisted of 72 respondents selected using consecutive sampling. Data collection used an adapted questionnaire from the 2017 Indonesian Demographic and Health Survey (IDHS). Bivariate data analysis was performed using the non-parametric Wilcoxon Signed-Rank Test. The respondent characteristics were dominated by the 16-17 years age group (91.7%) and females (54%). The results showed a significant decrease in the low knowledge category, from 72.2% before the intervention to 31.9% after the education. In the affective domain evaluation, the respondents' positive attitude spiked sharply from 2.8% to 45.8%. Statistical test results confirmed a significant effect of the educational intervention on both knowledge level (p 0.001) and attitude (p 0.001). The provision of reproductive health education significantly affects the increase in knowledge and improvement of adolescent attitudes about HIV/AIDS at SMAN 7 Bengkulu City. Schools are advised to integrate this educational program sustainably through collaboration with local health authorities.